Implementasi Profil Pelajar Pancasila Dalam Kurikulum Merdeka Mandiri Berubah Pada Pembelajaran Biologi Di SMA Kabupaten Kuningan - Karlina, Lilis; Hindriana, Anna Fitri; Nur, Sofyan Hasanuddin (Edubiologica, 2022)
Student Profile Pancasila, is the goal in the independent curriculum transformation, This independent curriculum also strengthens the achievement of the Pancasila student profile developed according to the themes determined by the government, where to become an outstanding and productive individual in the 21st century, one must have global abilities and character in accordance with Pancasila values. The characteristics of the Pancasila Student Profile are: having faith and devotion to the One Almighty God and noble character, global diversity, mutual cooperation, independence, critical thinking, and creativity. Analyzing the Pancasila Student Profile is developed in the learning process, in previous research, there has not been a study regarding the analysis of strengthening the Pancasila student profile. This research is qualitative research, involving participation from high school students in the 10th grade, with a total of 8 schools, data observation with analysis using triangulation. The aim is to analyze the strengthening of the Pancasila student profile in the learning process, viewed from the teaching module with 5 aspects, namely: a) The arrangement of learning objectives according to the achievement of Phase E learning and including prerequisite knowledge. b) Understanding of Biology according to Phase E. c) Project-based or case study learning. d) Literacy and numeracy. e) The Pancasila student profile in the independent curriculum seen from assessment. The implementation of strengthening the Pancasila student profile in biology learning shows that there are still deficiencies in 3 schools, especially in the arrangement of learning objectives, which are not appropriate because the competencies in the learning achievement are not stated and the strengthening of the Pancasila student profile is not included. Issues in project-based learning plans and issues in the module are not contextual and the measurement of biology understanding is in line with the Learning Outcomes, but the presentation of questions is not in accordance with the revised Bloom's taxonomy. The implementation of strengthening the Pancasila student profile in the learning process is crucial in efforts to improve the quality of education in Indonesia in accordance with the needs of the times.